Group III-V nanostructures application in gas sensing - Nyembe, Sanele G. (My University, 2018)
The advent of nanoscience and nanotechnology has made it possible to control several properties such as material shape, size and stability. However, different production approaches are often required. Engineered surfaces with tailor-made properties such as large surface area or specific reactivity are used routinely in a range of applications such as in fuel cells, catalysis, etc. Nanomaterials with unique morphologies have been developed and used in fields such as electronic device manufacture, chemistry and engineering. Synthesis of gold icosahedral (Ih) and decahedral (Dh) nanostructures was successfully achieved through a two-step heterogeneous nucleation process. Citrate stabilised seeds were used to grow these nanostructures. Cetyltrimethylammonium bromide (CTAB) was used to promote fast growth of Au nanostructure along the [111] crystal lattice plane. Dh and Ih nanostructures are known to be thermodynamically unfavourable above size of 5 nm. Successful growth of such nanostructures above this critical size limit was explained in terms growth kinetics. Gold nanostructures were found to have an average particle size of 50 nm and a narrow size distribution range of 45 nm to 55 nm. The seeds were fast-handled during growth to enhance the formation of these nanostructures. In-depth characterisation of these nanostructures confirmed that they formed via crystal twinning mechanism. Synthesis of gold nanostructures with different sizes was achieved through a three-step heterogeneous nucleation process. Different types of seeds were prepared using different stabilizers (Citrate and CTAB). Citrate and CTAB stabilized seeds were used to grow Au nanostructures separately. The CTAB stabilized seeds showed polydispersity, suggesting the presence of various shapes. These seeds produced agglomerated particles of various shapes with a wide particle diameter distribution ranging from 50 nm to 200 nm. The triangular Au nanostructures present in the mixture had a 3 dimensional morphology (i.e. pyramid shape) as confirmed by atomic force microscopy (AFM). The citrate stabilized seeds were monodisperse and they yielded well dispersed Au nanostructures with uniform morphologies. These Au nanostructures had an average particle size of 50 nm and a narrow size distribution range of 45 nm to 55 nm. iii Laser assisted synthesis of silicon nanowires (SiNWs) was achieved through the use of gold and nickel nanoparticles as catalysts. The diameter of the resulting SiNWs was found to be dependent on that of the catalyst. The gold catalysed silicon nanowires were unevenly curved and branched owing to the high kinetic energy possessed by gold nanoparticles (AuNPs) at relatively high processing temperature. The use of nickel as catalyst resulted in the formation of several SiNWs on a single nickel catalyst due to interconnection of the nickel metal particles at processing temperature. The morphology of SiNWs catalysed by both nickel and gold was controlled by optimising the laser energy during ablation. Indium phosphide nanowires (InPNWs) with an average diameter of 87 nm were successfully synthesized through thermal chemical vapour deposition (CVD) method. The smooth surface nanowires showed a relatively narrow size distribution of 70 nm to 105 nm. Temperature programmed deposition (TPD) was used to study the thermodynamic behaviour of gas desorption. The study revealed that gaseous CO and CH4 molecules bind to InPNW surface through chemical and physical adsorption. Redhead method was used to estimate the enthalpy energy of desorption for CO and CH4 to be 142 kJ/mol and 38 kJ/mol. The sorption temperature ranges were found to be 220 ̊C to 260 ̊C for CO and -50 ̊C to -20 ̊C for CH4. InPNWs were used to fabricate a gas sensor electronic device and were tested for performance. The device showed a quick response time of 29.19 s for CO at 250 ̊C. Indium arsenide nanowires (InAsNWs) with an average diameter of 45 nm were successfully synthesized using homogeneous catalysis approach and chemical vapour deposition method. Succesful synthesis of InAsNWs was achieved at a temperature of 700°C suggesting that solution-liquid-solid growth mechanism was involved. Synthesis conditions were optimised to minimise InAsNWs polytypism and stacking faults. The results showed that InAsNWs have significant adsorption sites and affinity for CO and H2S gases due to the formation of electron accumulating surface. The calculation of enthalpy energy of desorption revealed that interaction of InAsNWs and CO was through physisorption. InAsNWs showed a response time of 72s for CO at 250 ̊C. Characterization of the nanostructures was carried out using high resolution transmission electron microscope (HRTEM), Raman spectroscope, high resolution scanning electron microscope (HRSEM), UV-Vis spectrometer, X-ray diffractometer (XRD), temperature programmed desorption (TPD) and diffuse reflectance infrared Fourier transform spectroscope (DRIFTS).
A thesis submitted to the Faculty of Science, School of Chemistry at the University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Doctor of Philosophy, 2018
Keywords: Nanostructures; Nanotubes